The Disabled People Virtual Communities in Social Media from The Perspective of Public Sphere Theory - Nurul Hasfi; Turnomo Rahardjo (Ikatan Sarjana Komunikasi Indonesia, 2019)
Many researches view the internet as a virtual public sphere or forum potential that provides a space for minority groups to voice their opinions. This article identifies the role of social media in creating political public sphere for voters with disabilities in Indonesia during Presidential Election in 2019. By applying the normative values provided by Public Sphere Theory and Sphere Public Subaltern Theory, this article determines various potentials as well as stumbling blocks of the internet as a virtual public sphere for internet users. Virtual ethnography method is used to determine the identity of virtual communities of disabled people on three most active social media platforms in Indonesia, namely Instagram, Facebook and Twitter. Virtual Ethnography enables researchers to conduct an online observation on virtual communities three months prior to the 2019 Presidential Election. The data findings help the researchers draw conclusion that social media has technically advocated the endeavor of the disabled people’s political rights equality, proven by the existence of disabled people’s virtual communities and the narratives of struggle for their political rights equality. However, the data has shown an inadequacy of disabled people’s virtual community to create dynamic inter-activities between its members as this community has not been able to reflect a public sphere that is able to build public opinion which effectively influences public policy.